A famacocinética e os efeitos sedativos e comportamentais dos cloridratos de xilazina e de detomidina, administrados por diferentes vias, em asininos Nordestinos (Equus sinus) - Rosa, Ademir Cassiano da [UNESP] (2014)
The objectives of this study were to evaluate the pharmacokinetics, behavioral and sedative effects of xylazine and detomidine hydrochlorides administered by intravenous (IV) and intramuscular (IM) routes in northwestern donkeys. Six donkeys were used in phase I and eight donkeys in phase II. The methods used in both phases (I e II) were similar, except by pharmacokinetical analysis in phase II. IN phase I crescent doses of xylazine (0.1, 1.0 and 1.5 mg/kg) and detomidine (10, 20 and 30 μg/kg) by IV and IM routes, with the objective for selection of doses to be used in phase II. The behavioral and sedative effects were evaluated in phase I by variations in head height, ataxia degree and responses to sound together with the cardiorrespiratory variables. In phase II were harvested blood samples for analysis of plasma concentration of xylazine by intravenous and intramuscular routes in moments: before, and 1, 1.5, 2, 4, 6, 10, 15, 30, 60, 90, 180, 270, 360, 540, 720 minutes after administration. The plasma concentration of xylazine and detomidine were determined by HPLC and mass spectrometry. The tukey test was used for parametric, and Wilcoxon test for non-parametric variables. For comparison of plasma concentration and pharmacokinetical variables between routes and for the same sedative were used the t paired test (P<0.05). The lowest dose of IM xylazine did not cause sedation or cardiorrespiratory changes at any time after administration. The doses of 1.0 and 1.5 mg/kg had head drop from 20 to 45 and 60 minutes respectively, with predominance of mild ataxia with both doses. With 10, 20 and 30 μg/kg of IM detomidine was reduced head height between 30 and 60, 20 and 90, and up to 90 minutes respectively with predominance of mild ataxia in 10 and 20 doses and between mild and moderate with 30 μg/kg. By intravenous route 10 μg/kg of detomidine caused mild to moderate ataxia and head drop until 45 minutes. Doses of 20 and 30 μg/kg ...